XML Digital Watermarking - Khalid, Edris; Fakhreldin, Mohammed Adam Ibrahim; Jasni, Mohamad Zain; Tuty Asmawaty, Abdul Kadir (2013)
Due to the widespread and population of internet, digital data is copied and reproduced easily, which generate the high demand for copyright protection. Digital watermarking is one of the most efficient methods to protect the digital data. Digital watermarking is the process of hiding digital signal into digital document. The digital signal is called watermark. This paper covers the basic concepts of digital and XML watermarking